(untitled) (Fiep Bulletin - online, 2011)
Introduction: Bibliographic5 study, performed from May to July 2009, on LILACS and CINAHL’s databases, in which we respectively used the descriptors: trauma, child and pre-school children, according to the descriptors classification in health science (DECS), and health school and injuries. Objectives: to characterize, according to the scientific literature, children victims of trauma in the school environment; the main injuries and risk factors for these accidents; to identify the moment and the school area of major occurrence of trauma and how prevention to accidents is carried out. Results: Most accidents occur to male children belonging to the age group between 10 and 19 years old. Falls, among others, appear as the leading cause of injuries at school, for which the most propitious moment and place are school breaks and the playground, respectively. In this perspective, we realize how important it is that professionals develop awareness activities with children so that they can be able to identify the danger they are exposed to, aiming to avoid accidents and, as a consequence, improving the quality of life and the attendance to classes. Conclusions: we conclude that the school must play a key role in health protection and children welfare, aiming to ensure a safe environment for playing and developing school activities. The action of nursing professionals become, therefore, essential in the care of the victims, and it’s also their competence to develop preventive actions.